Dominant CD4‐dependent RNA‐dependent RNA polymerase‐specific T‐cell responses in children acutely infected with human enterovirus 71 and healthy adult controls. Issue 1 (May 2014) - Dang, Shuangsuo; Gao, Ning; Li, Yaping; Li, Mei; Wang, Xiufang; Jia, Xiaoli; Zhai, Song; Zhang, Xin; Liu, Jingkun; Deng, Huiling; Dong, Tao
Summary Human enterovirus 71 (EV71) is one of the major causes of hand, foot and mouth disease (HFMD), which leads to significant mortality in infected children. A prophylactic vaccine is urgently needed. However, little is known about the protective T‐cell immunity in individuals infected with the EV71 virus. In this study, we performed a comprehensive ex vivo interferon‐γ ELISPOT analysis in 31 children infected with EV71 as well as in 40 healthy adult controls of the CD4+ and CD8+ T‐cell responses to overlapping peptides spanning the VP1 structural protein and RNA‐dependent RNA polymerase (RdRp) non‐structural protein. EV71‐specific CD4 T‐cell responses were detected in most of the acute patients and were mostly CD4‐dependent RdRp‐specific responses. CD8‐dependent VP1 and RdRp‐specific responses were also detected in a small proportion of recently infected children. There was no significant association between the strength of the T‐cell responses and disease severity observed during the acute EV71 infection phase. Interestingly, an RdRp‐specific, but no VP1‐specific, CD4‐dependent T‐cell response was detected in 30% of the adult controls, and no T‐cell responses were detected in healthy children. In addition, 24 individual peptides containing potential T‐cell epitope regions were identified. The data suggest that CD4‐dependent RdRp‐specific T‐cell responses may play an important role in protective immunity, and the epitopes identified in this study should provide valuable information for future therapeutic and prophylactic vaccine design as well as basic research.